THE EFFECT OF ANXIETY ON FOREIGN LANGUAGE SPEAKING PERFORMANCE - Sadullayeva Parvina Bakhtiyorovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The effect of anxiety on foreign language speaking performance is one of the most widely discussed issues in the field of language learning. When people seek to communicate in a language that is not their mother tongue, they often experience certain  psychological  barriers  that  prevent  them  from  speaking  fluently  and confidently. Among the most common of these barriers is anxiety, a psychological state characterized  by  nervousness,  tension,  and  self-doubt  that  manifests  acutely  when expressing oneself in a foreign language context.